Correlation between students’ reading habits and their reading comprehension skills - Abdul Ayiz; Yuko Taniguchi (Early Publishing Group, 2025)
This study investigates the significant relationship between students' reading habits and their reading comprehension skills, a vital area within English Language Teaching (ELT) given the role of reading in language development and academic achievement. Effective reading strategies, habitual engagement with texts, and motivational factors are recognized as influential components of successful reading comprehension; however, the extent to which habitual reading behaviors predict comprehension performance remains underexplored, especially in formal educational settings. Current research emphasizes the importance of reading frequency, duration, and motivation but often lacks empirical evidence linking these habits directly to comprehension outcomes. The primary aim of this study is to examine whether specific reading habits—such as reading frequency, duration, and interests—are positively correlated with students’ reading comprehension skills. Utilizing a correlational research design, the study involved 120 Grade 11 students from a public high school in Indonesia, selected through stratified random sampling to ensure representativeness. Data collection was conducted via self-report questionnaires assessing reading habits and standardized reading comprehension tests. Data analysis employed statistical techniques such as correlation and regression analysis to identify relationships and predictive patterns between reading behaviors and comprehension scores. The findings reveal a significant positive association between frequent reading and higher comprehension levels, with sustained reading durations further enhancing understanding. Motivational attitudes towards reading also contributed to better comprehension performance, although personal preferences showed no significant impact. These results suggest that fostering regular reading practices and motivating students to read more frequently can substantially improve their comprehension skills. The study underscores the importance of promoting consistent reading habits in educational settings and provides empirical evidence to inform curriculum design and teaching strategies aimed at enhancing literacy development. Ultimately, encouraging habitual reading, alongside cultivating positive attitudes, can lead to improved language proficiency and academic success among students learning English as a foreign language.